Case Report: Combined pembrolizumab, 5-fluorouracil, and cisplatin therapy were remarkably effective in p16-positive squamous cell carcinoma of unknown primary - Suzuki, Risako; Hamada, Kazuyuki; Ohkuma, Ryotaro; Homma, Mayumi; Tsurui, Toshiaki; Iriguchi, Nana; Ishiguro, Tomoyuki; Hirasawa, Yuya; Ariizumi, Hirotsugu; Kubota, Yutaro; Horiike, Atsushi; Yoshimura, Kiyoshi; et al. (Frontiers in Oncology, 2023)
Background Cancer of unknown primary (CUP) is a malignant tumor without a known primary lesion with a frequency of 3−5%. It can be divided into favorable and unfavorable prognosis subsets. While recommended treatments are available for the former group, there is no established treatment for the latter. Here, we report the effective treatment of a 32-year-old woman with p16-positive squamous cell CUP with pembrolizumab plus 5-fluorouracil and cisplatin therapy. Case presentation A 32-year-old woman presented with metastatic lesions in the liver, lung, bone, cervical region, abdominal region, and pelvic lymph nodes. She was diagnosed with p16-positive squamous cell carcinoma of unknown primary origin. The patient received pembrolizumab plus 5-fluorouracil and cisplatin therapy, which markedly reduced the metastasis and improved her Eastern Cooperative Oncology Group performance status after two courses. Conclusion This case report highlights the potential of pembrolizumab plus 5-fluorouracil and cisplatin therapy for treating CUP with an unfavorable prognosis. p16 positivity is worth examining for squamous cell carcinoma of unknown primary origin, and if present, this therapy should be considered a promising treatment option.